Pendampingan Guru dalam Pengajaran Otomasi Industri untuk Menghadapi Era Industri 4.0 di SMK 1 Cikarang - Setiawan, Setiawan; Susanto, Nanang; Nasihardani, Dana; Rahmawati, Puput (Pakis Journal Institute, 2025)
This community service program was implemented to enhance teacher competencies in industrial automation instruction at SMK 1 Cikarang Pusat in response to the growing demands of Industri 4.0–oriented vocational education. Initial assessments identified key challenges, including limited teacher mastery of modern automation technologies, suboptimal integration of automation content within the curriculum, insufficiently representative laboratory facilities, and low engagement in industrial partnerships. The assistance program was designed through a series of stages comprising stakeholder socialization, practice-oriented technical training on PLC, HMI, sensors, actuators, and IoT, technology implementation through the installation of automation equipment and the development of a mini teaching factory, as well as structured mentoring and evaluation to ensure effective competency transfer. Sustainability efforts were strengthened through the development of updated learning modules, collaborative curriculum refinement, and the establishment of an industry link-and-match forum. The program is expected to improve teachers’ pedagogical and technical capabilities and enhance graduates’ readiness to meet Industri 4.0 workforce standards.